PENGARUH BIMBINGAN KELOMPOK TERHADAP KEPERCAYAAN DIRI PESERTA DIDIK KELAS X SMA NEGERI 5 PONTIANAK - Audia, Olga; Asrori, M.; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGroup guidance services are a process of providing assistance provided to individuals to help students solve problems and achieve optimal development conducted in groups. The better the implementation of group guidance services the higher the confidence level of learnersTherefore, the researcher wanted to know more about how big the influence of group guidance service to the students' self confidence X class SMA Negeri 5 Pontianak. The general problem of this research is